Trust in justice and the legitimacy of legal authorities: topline findings from a European comparative study - Bradford, B. (2013)
Issues of public trust in justice and institutional legitimacy are becoming increasingly salient in debate about criminal justice across Europe. Legitimate authority can be defined as having three interlinked elements: (a) legality (acting according to the law); (b) shared values (values that are shared by those with authority and those subject to that authority); and (c) consent (the sense amongst the policed of a moral obligation to obey the authority). According to this definition, legitimacy is present not only when individuals recognise the authority of institutions and feel a corresponding duty of deference to them (consent); it is also present when individuals believe that justice institutions have a proper moral purpose (shared values), and that justice institutions follow their own rules as well as the rules that govern everyone in society (legality). With this definition in mind, we analyse in this chapter data from the fifth European Social Survey on relationships between public trust in justice institutions and public perceptions of the legitimacy of these institutions